Illocutionary Acts of Dave Chappelle’s Stand-up Comedy The Closer - Kaban, Sahat Parulian Prantinus; Rido, Akhyar (Universitas Teknokrat Indonesia, 2024)
This study examines the use of illocutionary acts in Dave Chappelle's stand-up comedy The Closer, focusing on its micro classes and literal meanings. Utilizing the framework established by Searle (1969) and employing a qualitative methodology, this study collects the data through library research. The findings reveal that Dave Chappelle’s stand-up comedy uses four micro classes of illocutionary acts, consisting of assertive, directive, expressive, and commissive. Assertive acts become the most prevalent micro classes used by Dave Chappelle (604 data), indicating his authority delivery by asking questions, giving comments, or making requests. After that, directive acts are used to engage the audiences during the performance (74 data) by using personal anecdotes. Following that, expressive acts are utilized to show his emotional connection to the content (42 data) through conveying his psychological state. Finally, commissive acts are employed to indicate commitment on his personal concern (17 data) by making promises or expressing his intention. To conclude, this study provides better understanding of stand-up comedy as a performative speech blending humor with social commentary. Future study should explore audience reception to better understand comedic performances' societal impact.Keywords: Illocutionary Acts, micro classes, stand-up comedy, Dave Chappelle.